CHALLENGES IN ORTHO-PERIO AND GENERAL DENTISTRY INTERRELATIONSHIP. LIMITS AND PERSPECTIVES - I.Luchian; Ioana Vata; Ioana Martu; Monica Tatarciuc; Pendefunda Valeria; Silvia Martu (Romanian Society of Oral Rehabilitation, 2016)
Orthodontic treatment has become nowadays more popular than ever. The time when orthodontic treatment was just addressing to children has long passed. We are dealing now with a lot of adult cases that are more difficult to treat and raise many problems not only from the specialist cooperation but also from the ethical perspective. In the end of every orthodontic treatment we should focus only on one thing: the outcome. The outcome of an orthodontic treatment is not only a perfectly aligned row of teeth, it's a sum of many periodontal aspects viewed from a very critical and ethical point of view. Although dental medicine is a liberal profession in which most of the patients have to pay the costs of the treatments privately this is no excuse to ignore the ethical dimension and not to give the patient the right to have access to the best possible specialized interdisciplinary care, autonomy and, self-determination